Identity During a Pandemic: COVID-19 and Ethnic Divisions in the United States - Guzman Debnam, Jakina; Mabeu, Marie Christelle; Pongou, Roland (Université d'Ottawa | University of Ottawa, 2021)
Mobility restrictions have been imposed on over half of the world's population as part of efforts to slow the spread of the novel coronavirus. Given the economic and psychological expense of these policies, understanding how their benefits depend on structural factors is critical for optimal policy design. We find causal evidence that the effectiveness of mobility-restricting policies in the United States has been critically constrained by ethnic divisions-U.S. counties with high levels of ethnic divisions fared worse than their less-divided counterparts after lockdowns in both COVID-19 cases and related deaths. This is especially true in areas with higher racial segregation. Following President Trump's State of Emergency declaration, a one standard deviation increase in the ethnic fragmentation index (EFI) in the most racially segregated counties increased COVID-19 cases and associated deaths by 1; 014 and 63, respectively; in the least segregated counties these outcomes are 112 and 4, respectively. These results highlight that ethnic divisions, rather than ethnic diversity, spurred drastic differences in COVID-19's impact. Consistent with less effective mobility restrictions in more ethnically divided counties, we find smaller mobility reductions and less mask-wearing in these counties following policy implementation. These results are not driven by a lack of physical public goods or by socioeconomic differences. Instead, we interpret our findings as the result of mobility restriction policies' imperfect enforceability. Where ethnic divisions are present, communication is sparser, pro-social norms are weaker, and communities are less able to enforce adherence by enacting social sanctions. Our results suggest that policies promoting ethnic and racial integration can allay the negative social and economic impacts of contagious disease by decreasing the likelihood of disease spread.
Keywords: 2101E; COVID-19; Ethnic Identity; Ethnic divisions; Racial segregation; Diversity with(out) divisions; Lockdown Policies; Mobility restrictions; Physical distancing; Mask Wearing; Pro-social Norms